2019
DOI: 10.1002/ente.201900589
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Energy Storage Device Based on LiMn2O4 (Spinel) Positive Electrode and Anthraquinone‐Modified Carbon‐Negative Electrode

Abstract: This article describes the design and tests of aqueous hybrid energy‐storage devices based on activated carbon‐negative electrode and LiMn2O4 (spinel) positive electrode. For this study, activated carbons from two different sources are selected and are further improved by grafting with electroactive anthraquinone molecules. The electrolyte solution is aqueous 1 m Li2SO4 with pH = 7.5. The performances of balanced hybrid devices are characterized by cyclic voltammetry and galvanostatic measurements. It is possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…These results should be highlighted when compared to other Li-HSCs based on LiMn 2 O 4 , ,,, (Figure c). Recently, Li et al reported a cell based on LiMn 2 O 4 nanorods as the cathode, activated carbon (AC) as the anode, and 1 M lithium hexafluorophosphate (LiPF 6 ) in a mixture of ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) as the electrolyte .…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…These results should be highlighted when compared to other Li-HSCs based on LiMn 2 O 4 , ,,, (Figure c). Recently, Li et al reported a cell based on LiMn 2 O 4 nanorods as the cathode, activated carbon (AC) as the anode, and 1 M lithium hexafluorophosphate (LiPF 6 ) in a mixture of ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) as the electrolyte .…”
Section: Resultsmentioning
confidence: 73%
“…The aqueous cell containing this mixed oxide operates at 1.6 V and is capable of reaching 20 W h kg –1 at 264 W kg –1 . Superior performance in aqueous media was reported by Hanna et al using LiMn 2 O 4 as a positive electrode and activated carbon as the negative electrode containing electroactive anthraquinone molecules. This cell operates at 1.5 V in 1 M Li 2 SO 4 (pH = 7.5) and is capable of reaching an energy density of 30–35 W h kg –1 and a power density of 25–33 W kg –1 .…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Composite of anthraquinone with reduced graphene oxide and carbons with quinone functionalities have demonstrated enhanced capacitance as electrode materials [59e61]. Hybrid device based on LiMn 2 O 4 as a positive electrode and anthraquinone-modified carbon as a negative electrode in 1 mol L À1 Li 2 SO 4 is a good strategy to enhance energy and power parameters [62], and determining correct amount of anthraquinone loading on carbon appears to be key for achieving optimized performance [63]. Redox activity of PPD in aqueous KOH greatly enhances the delivered capacitance of the hybrid cell [26], and high self-discharge in PPD-based cells could be solved by its covalent bonding to carbon surface [64].…”
Section: Equilibrium Potential and Hybrid Cell Performancementioning
confidence: 99%